Cutaneous malakoplakia presenting as a groin swelling and graft failure. Issue 4 (23rd April 2019) - Macdonald, Ross Andrew; Moyes, Colin; Clancy, Marc; Douglas, Peter
Abstract : Malakoplakia (from the Greek malakos, 'soft' and plakos 'plaque') is a granulomatous inflammatory condition, commonly presenting as a plaque in the genitourinary system, but has been shown to affect a wide variety of structures including the skin. Presentation is varied and a high degree of clinical suspicion is needed to make a diagnosis. We report a case of cutaneous malakoplakia presenting as an inguinal swelling in a 48-year-old kidney transplant patient with temporally associated graft dysfunction. New groin swelling in an immunosuppressed patient often prompts investigation centred on a malignant cause. While this is often appropriate, less common infectious and inflammatory causes should be considered. This case highlights the importance of thorough workup and investigation, including histopathology, in immunosuppressed cohorts and acts as a reminder that less common and more complex diagnoses warrant consideration in this group.